Seasonal variability of eddy kinetic energy in the East Australian current region - Liu, Jia; Zheng, Shaojun; Feng, Ming; Xie, Lingling; Feng, Baoxin; Liang, Peng; Wang, Lei; Yang, Lina; Yan, Li (Frontiers in Marine Science, 2022)
Based on satellite altimeter observations and an eddy-resolving ocean general circulation model (OGCM) for the Earth Simulator (OFES) output, the seasonal variability of mesoscale eddy kinetic energy (EKE) and its associated dynamic mechanism in the East Australian Current (EAC) region are studied. High EKE is mainly concentrated in the shear-region between the poleward EAC southern extension and the equatorward EAC recirculation along Australia's east coast, which is confined within the upper ocean (0-300 m). EKE in this area exhibits obvious seasonal variation, strong in austral summer with maximum (465±89 cm² s-²) in February and weak in winter with minimum (334±48 cm² s-²) in August. Energetics analysis from OFES suggests that the seasonal variability of EKE is modulated by the mixed instabilities composed of barotropic and baroclinic instabilities confined within the upper ocean, and barotropic instability (baroclinic instability) is the main energy source of EKE in austral summer (winter). The barotropic process is mainly modulated by the zonal shear of meridional velocities of the EAC southern extension and the EAC recirculation. The poleward EAC southern extension and the equatorward EAC recirculation are synchronously strengthened (weakened) due to the local high (low) sea level anomalies (SLA) under geostrophic equilibrium, and the barotropic instability dominated by zonal shear is enhanced (slackened), furthermore, it results in a high (low) level of EKE in the EAC region.